Air Pollution Exposure with Fine Dust. Responses in the Pulmonary Vasculature and the Right Heart - Durmus, Nedim (Ann Am Thorac Soc, 2018)
Detrimental effects of air pollution with fine dust (particulate matter ≤2.5 μm in aerodynamic diameter, or PM(2.5)) on the systemic circulation and the left heart have been studied intensely during the past decade. In comparison, knowledge regarding the effects of exposure to air pollution with PM(2.5) on the pulmonary vasculature and the right heart lags far behind. A report on severe lung disease and right heart failure in coal miners was published nearly 170 years ago. However, today, we still do not have a clear picture of how the effect of air pollution on the pulmonary circulation or the right heart should be viewed from a clinical, mechanistic biological, therapeutic, or economic angle. In the laboratory, we have established a model of immune response–induced vascular remodeling that is significantly worsened by adding PM(2.5) to the intranasal antigen challenge solution. Importantly, the PM(2.5) is given at a concentration that by itself does not induce significant inflammation or pulmonary vascular remodeling. However, when added to antigen, this low-dose PM(2.5) exposure induces severe pulmonary vascular remodeling, significantly increased right ventricular pressures, and significant molecular changes in the right heart. Our data also show that these PM(2.5)-exaggerated responses are dependent on interleukin-13, interleukin-17A, and antigen-specific antibody. The experimental model is being used to address a few questions: 1. Which mechanism protects the animals from severe right ventricular failure despite the severity of the pulmonary artery remodeling? 2. What is the mechanism by which PM(2.5) worsens the response to antigen? 3. How does PM(2.5) exert its effects across the small airways to the small blood vessels? In conclusion, further investigation is urgently needed to understand the effects of exposure to ambient or occupational air pollution on the pulmonary vasculature, because better knowledge could lead to immediate beneficial actions for patients with pulmonary hypertension and persons at risk.